Analisis Debit Air Irigasi (Suplai dan Kebutuhan) di Sekampung Sistem - Sembiring, Christa Emanuel (UNIVERSITAS LAMPUNG, 2016)
Sekampung system is one of national granary in Lampung Province. The needs of irrigation water to irrigate rice fields in Sekampung system which supplied from Argoguruh weir. Sekampung System has two (2) Feeder Canals, namely Feeder Canal I and II. Feeder Canal I serve four (4) Irrigation areas namely Sekampung Batanghari, Sekampung Bunut, Batanghari Utara, and Raman Utara while the Feeder Canal II serve three (3) irrigation areas namely Bekri, Punggur Utara, and Rumbia Barat. The problem were the ability of supply irrigation water discharge from Argoguruh weir, the large discharge irrigation received in the furthest of each secondary Canal in Sekampung System irrigation areas, the length of time needs which started from Argoguruh weir to the irrigation area in Sekampung System, and the condition of irrigation network ability in sekampung system. The result showed that Argoguruh weir was not able to supply irrigation water throughout the irrigation area in Sekampung system as needed. The decline in discharge irrigation water supplied by argoguruh weir until throughout the irrigation area in sekampung system, deceleration time of drainage throughout the irrigation area in Sekampung system and a decline of significant irrigation networks function ability in Sekampung System.